A estrutura organizacional frente as estratégias de aquisição: um estudo de casos em Minas Gerais - Bethania Mendes de Brito Antunes (2002)
This present paper has analyzed the transformations occurred in the structures of enterprises submitted to an acquiring process. The paper structure contemplates at a first moment, a conceptual discussion that recovers the view aspects of an organizational structure understanding, known as traditional, within an evolutionary perspective that pays off for the environment and recent changes, which have altered the organizational modus operandi. This framework gave opportunity of a data survey through documents analysis and semi-structured interviews, and, also a posterior discussion of aspects involving acquisitions and their analysis, from cases occurred in Minas Gerais, which have been chosen after a preliminary mapping and adjustments to the studytarget. The results met hereby have demonstrated that the acquisitions have affected the studied enterprises structures, as for down sizing hierarchic levels as for functional sizing. This has generated less formalization and bigger decisive decentralization, thus,improving the existent communication procedures. Another fact to be considered evinces that the structure integration process level and pace of the acquired, as well as the acquiring, strongly depends on both side goals, whatever concerns the efficiency aimed. Strategic goals that lead to acquisition are fundamental for the structure conduction, and the process dynamics is determinant for the acquiring strategy success.